Effects of two recovery procedures after a football game on sensory and biochemical markers - Kawczynski, A.; Mroczek, D.; Frackiewicz, A.; Chmura, P.; Becella, L.; Samani, A.; Madeleine, P.; Chmura, J. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The aim of this study was to investigate recovery processes on pressure pain sensitivity and blood indicators in professional football players after three different post-game training modalities: standard recovery training, no physical activity, delayed onset muscle soreness reduction training.